Mental fatigue changes from regular season to play-offs in semiprofessional soccer: A comparison by training days - Díaz-García, J.; Filipas, L.; La Torre, A.; Gómez-Rivera, J.; Rubio-Morales, A.; García-Calvo, T. (Scandinavian Journal of Medicine & Science in Sports, 2023)
The main purpose was to compare by each training the mental load and fatigue reported by semiprofessional soccer players comparing between regular season phase and the play-offs. Fifty-three players (Mage = 24.59 years) for two teams participated during the 2020/21 season. Mental load was measured with a Likert questionnaire. Mental fatigue was quantified with a Visual Analogue Scale. Four trainings were recorded each week (Monday = MD+1, Wednesday = MD-4, Thursday = MD-3 and Saturday = MD-1), with a competitive match on Sunday across 10 weeks (five dates of regular season - five dates of play-offs). A Linear Mixed Model was performed with R-studio, using the training days and the competitive phase as independent variables. The influence of time played as co-variable was also checked. Results showed MD+1 as the more mentally fatiguing day in both phases, although MD-4 were the training with higher mental load reported (p = 0.001). Comparing phases, mental fatigue was significantly higher during the play-offs (p = 0.037). With regard time played, players that did not usually play showed a decrease in mental load during the play-offs. Then, we recommend coaches to use recovery strategies for mental fatigue, avoid mentally fatiguing tasks close to competition and considerer the time played as a factor which may contribute to individual differences in player mental fatigue.